Urban mobility with a focus on gender: The case of a middle-income Latin American city - Olivieri, Cecilia; Fageda, Xavier (Journal of Transport Geography, 2021)
This study analyzes gender differences in travel patterns for the Metropolitan Area of Montevideo, Uruguay. By applying multilevel regression models, it provides estimates of the impact of individual and contextual factors on travel behavior. The paper's findings lend support to the household responsibility hypothesis, which claims that women's travel patterns are affected by the type of household in which they live and the consequent responsibilities or roles they assume. Furthermore, gender differences in travel patterns are reinforced across census tracts. The results indicate that policy makers need to consider gender differences when seeking to enhance urban planning decisions. © 2021 Elsevier Ltd
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; discipline; déplacements urbains; environnement; géographie; géographie urbaine; projet charge mentale; périodes historiques; régions géographiques; sciences humaines; thématiques; travail; uruguay

Gender and water insecurity in a subarctic Indigenous community - Hanrahan, Maura; Mercer, Nicholas (The Canadian Geographer / Le Géographe canadien, 2019)
Indigenous communities in Canada suffer disproportionately from compromised water insecurity, with multiple negative implications. Some attention has been paid to gender and water insecurity in developing countries, especially in sub-Saharan Africa, but the topic has been neglected for subarctic settings. We conducted long-term research in Black Tickle, a remote Inuit community in Labrador, Canada, with no piped water and limited access to potable water. Our research was aimed at understanding the multiple dimensions of water security, identifying materialist responses, and conducting a pilot project in domestic rainwater harvesting. Water security emerged as a gendered phenomenon. We supplemented our reflective analysis on this research with two focus group discussions during which Inuit women described their experiences of water security. Participants reported that their physical and mental health are undermined by water insecurity and that water is a source of multiple stresses that demand resilience. Given a developing remittance economy, gender was identified as an increasingly significant determinant of water insecurity in this subarctic community. Having to retrieve water themselves, Inuit women experience altered gender norms and a persistent values conflict in addition to physical strain. Water acquisition is an added responsibility, impacting their labour load. Alternatively, in relying on available men to retrieve water, participants reported feeling guilty and anxious and they worried about men fetching water in dangerous weather conditions and in the vicinity of dangerous wildlife. Participants’ experiences make clear the urgency for a materialist response to water insecurity in the Indigenous subarctic.
Keywords: 2000 à aujourd'hui; accès à l'eau; amériques; canada; communauté Inuit; discipline; environnement; géographie; géographie féministe; labrador; projet charge mentale; périodes historiques; régions géographiques; santé; sciences humaines; thématiques

Les Amériques créatives: regards croisés sur les discours et les pratiques - Pujol, Charlotte; Doré, Émilie; Drouilleau, Félicie; Villafuerte, Susana; Tinteroff Gil, Vanessa (L'Harmattan, 2017)
"Des civilisations précolombiennes à l'American Way of Life, les A mériques ont constitué un espace propice aux mythes et aux utopies. Terres de migrations, parfois forcées, elles sont constituées de multiples lieux de rencontres, de conflits, d'échanges culturels. Aujourd'hui les phénomènes d'innovation technologique, identitaire ou politique témoignent du fait que les Amériques, du Nord au Sud, demeurent un terreau de créativité. La créativité repose sur la capacité des acteurs à imaginer un autre cadre que celui dans lequel ils sont immergés. Aussi cet ouvrage s'attarde-t-il sur les discours et les pratiques individuels ou collectifs, discrets ou médiatisés, improvisés ou programmés qui participent à la fabrique des espaces et des sociétés. La diversité des regards et des situations analysées se traduit par la multi disciplinarité de ces pages. Sociologues, anthropologues, historiens, juristes, géographes, spécialistes de la littérature, du cinéma, du théâtre ou de la musique proposent des analyses ancrées dans la réalité ; leurs points de vue sont autant d'illustrations des processus créatifs. Il ne s'agissait pas là de chercher une improbable exhaustivité, mais bien plutôt de tenter de mettre en lumière la façon dont la force créative des individus et des groupes jalonne l'histoire et le devenir des nations américaines. C'est donc un kaléidoscope qui est proposé aux lecteurs, une diversité d'approches qui les font voyager de l'Alaska au Brésil."–Page 4 de la couverture
Le chapitre Nagels, Nora, 2017, « Créativité clientéliste des organisations de femmes populaires liées à l’alimentation à Lima », a été donné en lecture au cours POL4022.
Keywords: DIG; agriculture; amériques; anthropologie; arts; care; corps; cours; création; danse; discipline; environnement; géographie; musique; pol4022; premier cycle; régions géographiques; sciences humaines; sociologie; thématiques

Durable mais inégalitaire : la ville - Raibaud, Yves (Travail, genre et sociétés, 2015)
Cet article interroge des projets urbains qui semblent faire consensus dans les villes européennes (pénalisation du trafic automobile intra-urbain, encouragement du deux-roues motorisé, du vélo et de la marche à pied, du tramway et des autres transports en commun, du covoiturage) du point de vue des inégalités femmes hommes, à partir d’une série de recherches menées sur l’agglomération urbaine de Bordeaux (France). L’analyse d’une enquête sur les mobilités montre en effet que les femmes seraient défavorisées par ces mesures, aussi bien en raison des tâches qui leurs sont majoritairement dévolues (accompagnement des enfants, des personnes âgées, courses etc.), par le fait qu’elles ont une moins grande habileté dans les mobilités alternatives, ou par le sentiment de leur vulnérabilité dans l’espace public (crainte de l’agression dans certains quartiers et la nuit). A qui profite la ville durable ? Comment et où se décident ses nouveaux usages ? Comment se mettent en place les changements de comportements nécessaires à cette transition vers une ville que ses promoteurs décrivent comme douce, calme, belle, apaisée ? Cet article pose l’hypothèse que les bonnes pratiques de la ville durable ressemblent fort à de nouveaux habits de la domination masculine.
Keywords: discipline; environnement; espace urbain; europe; france; géographie; projet charge mentale; régions géographiques; sciences humaines; thématiques

La ville, faite par et pour les hommes : dans l'espace urbain, une mixité en trompe-l'œil - Raibaud, Yves (Belin, 2015)
Des noms d'hommes sur les plaques à tous les coins de rues. Des loisirs qui profitent en priorité aux garçons. Des offres de transport insensibles aux spécificités de genre. Sans oublier la culture du harcèlement.La ville se décline surtout au masculin. Plusieurs études récentes le confirment. L'auteur décrit comment la cité renforce les inégalités entre les femmes et les hommes et en crée de nouvelles, et montre qu'il est possible de la rendre plus égalitaire.
Keywords: discipline; domination masculine; environnement; europe; france; géographie; géographie du genre; organisation des villes; projet charge mentale; régions géographiques; sciences humaines; thématiques; violences; violences envers les femmes*

Geographies of privilege - Twine, France Winddance; Gardener, Bradley (Routledge, 2013)
How are social inequalities experienced, reproduced and challenged in local, global and transnational spaces? What role does the control of space play in distribution of crucial resources and forms of capital (housing, education, pleasure, leisure, social relationships)? The case studies in Geographies of Privilege demonstrate how power operates and is activated within local, national, and global networks. Twine and Gardener have put together a collection that analyzes how the centrality of spaces (domestic, institutional, leisure, educational) are central to the production, maintenance and transformation of inequalities. The collected readings show how power–in the form of economic, social, symbolic, and cultural capital–is employed and experienced. The volume's contributors take the reader to diverse sites, including brothels, blues clubs, dance clubs, elite schools, detention centers, advocacy organizations, and public sidewalks in Canada, Italy, Spain, United Arab Emirates, Mozambique, South Africa, and the United States. Geographies of Privilege is the perfect teaching tool for courses on social problems, race, class and gender in Geography, Sociology and Anthropology.
Keywords: afrique; afrique du sud; amériques; anthropologie; approches et analyses; canada; classe sociale; discipline; environnement; espagne; europe; géographie; italie; mozambique; outils; ouvrages de références; privilèges; racisme; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; émirats arabes unis; états-unis

Sustainable development, water resources management and women's empowerment: The Wanaraniya water project in Sri Lanka - Aladuwaka S.; Momsen J. (Gender and Development, 2010)
Water is one of the most important natural resources, and its effective management is essential given its scarcity. In rural Sri Lanka, the management of available water resources needs special attention because investment for water resource improvement is hard to obtain, and water itself is relatively scarce in the drier areas of the country. The Wanaraniya Water Project pipes water 6.5km from its source to individual houses in the village, saving women daily time and effort. The project is founded on commitments to community participation and the adoption of local knowledge. It was initiated by women, and has been operated and managed by them for the last six years. This study argues that the project can serve as a model for better planning of water management, and focuses on the unique strategies and innovative methods that have been used. In particular, it shows the impact of involvement in the project on women’s empowerment. The implementation of the project has helped women to improve their leadership qualities, confidence, self-reliance, and gain more power in the community through their successful establishment of a village water supply.
Keywords: approches et analyses; asie; cours; discipline; développement; développement participatif; environnement; géographie; histoire et politique; justice sociale; pol4022; premier cycle; ressource en ligne; régions géographiques; sciences humaines; sri lanka; thématiques; études de genres

Gendered geographies of environmental injustice - Buckingham, Susan; Kulcur, Rakibe (Antipode, 2009)
As environmental justice concerns become more widely embedded in environmental organizations and policymaking, and increasingly the focus of academic study, the gender dimension dissolves into an exclusive focus on race/ethnicity and class/income. While grassroots campaigning activities were often dominated by women, in the more institutionalized activities of organizations dominated by salaried professionals, gender inequality is neglected as a vector of environmental injustice, and addressing this inequality is not considered a strategy for redress. This paper explores some of the reasons why this may be so, which include a lack of visibility of gendered environmental injustice; professional campaigning organizations which are themselves gender blind; institutions at a range of scales which are still structured by gender (as well as class and race) inequalities; and an intellectual academy which continues to marginalize the study of gender—and women's—inequality. The authors draw on experience of environmental activism, participant observation, and other qualitative research into the gendering of environmental activity, to first explore the constructions of scale to see how this might limit a gender-fair approach to environmental justice. Following this, the practice of “gender mainstreaming” in environmental organizations and institutions will be examined, demonstrating how this is limited in scope and fails to impact on the gendering of environmental injustice.
Keywords: approches et analyses; corps; discipline; environnement; géographie; intersectionnalité; justice environnementale; justice sociale; projet charge mentale; sciences humaines; thématiques

«Je pensais que je pourrais avoir une relation plus egalitaire avec un Europeen.» Le rôle du genre et des imaginaires geographiques dans la migration des femmes - Riaño, Yvonne; Baghdadi, Nadia (Nouvelles Questions Féministes, 2007)
Le nombre de femmes migrant vers la Suisse en provenance de pays extérieurs à l'Union européenne a considérablement augmenté ces dernières années. La féminisation de la migration a été conceptualisée dans la littérature comme une conséquence des forces économiques mondiales et comme la seule option pour les femmes des pays à faible revenu pour résoudre leurs besoins matériels. Cet article soutient que cette perspective est insuffisante pour expliquer la migration féminine. Sur la base d'une analyse qualitative des récits de vie de vingt femmes d'Amérique latine, d'Europe du Sud-Est et du Moyen-Orient, nous concluons que de nombreux facteurs autres que les difficultés économiques influencent les décisions des femmes de migrer. En particulier, le désir d'atteindre l'égalité des sexes dans la société au sens large et au niveau du ménage semble être une forte motivation à la migration. Les images positives de l'Europe, des Européens et des relations de genre en Europe favorisent des pays comme la Suisse comme destination de migration. Nous concluons que lorsque les femmes traversent les frontières, elles construisent et reconstruisent le genre, et que le genre façonne leurs schémas migratoires.
Keywords: cours; discipline; environnement; europe; femmes immigrantes; géographie; géographie du genre; récits de vie; régions géographiques; sciences humaines; soc1061; sociologie; suisse; thématiques; travail

The nature of gender: work, gender, and environment - Nightingale, Andrea (Environment and Planning D: Society and Space, 2006)
Le genre est depuis longtemps reconnu comme important dans les questions environnementales, mais la manière de conceptualiser le lien entre genre et environnement fait l’objet de nombreux débats. Les théories féministes sur les femmes et le genre ont évolué, tout comme les conceptualisations sur le genre et l’environnement, ce qui a donné lieu à un débat clé au sein de l’écoféminisme et des littératures associées sur la question de savoir s’il existe une relation essentielle ou contingente entre les femmes et les environnements naturels. En géographie, la plupart des écologistes politiques partent du principe que le lien entre genre et environnement est une relation contingente, et étudient donc la manière dont les relations de genre sont saillantes dans la construction symbolique et matérielle des questions environnementales. Dans cet article, je cherche à m’appuyer sur ce travail et à soulever à nouveau la question de la manière dont le genre est conceptualisé par rapport à l’environnement. Je commence par passer brièvement en revue certains des travaux qui ont été réalisés sur le genre et l’environnement, puis je m’inspire du féminisme post-structural pour suggérer que le genre lui-même a été sous-théorisé dans les travaux sur l’environnement. Une fois que le genre est reconceptualisé en tant que processus, la relation dynamique entre le genre, l’environnement et d’autres aspects de la vie sociale et culturelle peut être mise en évidence. Il en ressort que les écologistes politiques doivent examiner la question du genre au-delà du foyer et de la communauté, et reconceptualiser le lien entre le genre et l’environnement. Une étude de cas sur la foresterie communautaire au Népal est utilisée pour illustrer l’importance d’interroger les processus par lesquels les relations entre les sexes deviennent saillantes et sont reproduites symboliquement et matériellement.
Keywords: approches et analyses; asie; discipline; environnement; géographie; histoire et politique; népal; politique écologique; post-structuralisme; projet charge mentale; régions géographiques; sciences humaines; sociologie; thématiques; écoféminisme

Suzanne MacKenzie Memorial Lecture conceptually unclad: feminist geography and Aboriginal peoples * - Peters, Evelyn J. (The Canadian Geographer, 2004)
This paper argues that feminist geography can provide some useful lessons in an attempt to increase Aboriginal peoples' representation in geography. It asks the question: How can we use the example of feminist geography to think about a geography that is more inclusive of Aboriginal people? The paper focuses on the issues of content in teaching, drawing on examples from urban and social geography, and on methodological challenges, especially the issue of reflexivity. Feminist geographer Suzanne Mackenzie argued that an emerging feminist geography left the discipline ‘conceptually unclad’, challenging scholars to consider new theoretical frameworks and new perspectives. I argue that emphasising the geographies of Aboriginal people also enriches geography, including feminist geography.
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; cours; discipline; démographie; environnement; féminisme autochtone; géographie; géographie féministe; géographie urbaine; histoire et politique; méthodologie; pol4105; premier cycle; périodes historiques; sciences humaines; thématiques